Viabilização da capacitação profissional e empreendedora no ramo da refrigeração - PEREIRA, Thalita Lobato (2025)
The objective of this study was to develop an interactive e-book aimed at the technical and entrepreneurial training of refrigeration mechanics, focusing on professionalization, formalization of services and introduction to the fundamentals of intellectual property, especially with regard to trademark registration. The proposal arose from the identification of a significant gap in the supply of accessible and specific teaching materials for this audience, whose activities in the market often lack technical support and guidance regarding the structuring of formal businesses and the construction of professional identity. The methodology adopted to carry out this work was qualitative in nature, with an exploratory and descriptive approach. Bibliographic research and a field survey were carried out with professionals in the refrigeration area in the city of São Luís, Maranhão. The e-book, conceived as a technical-pedagogical product, was structured in thematic modules that cover everything from fundamental refrigeration concepts to content related to business management, customer service, business formalization and practical guidelines for trademark registration. The results obtained demonstrate the significant contribution of the material to expanding the technical knowledge of participants, as well as to encouraging the formalization of their commercial activities. A strengthening of professional identity was also observed, made possible by the creation of their own brands, in addition to noticeable improvements in the quality of services provided. The e-book demonstrated the potential to positively impact the strategic organization of professionals in the sector, promoting the reduction of operational costs and boosting the development of the entrepreneurial ecosystem in the refrigeration area. In this way, this work not only fills an important training gap, but also offers a practical and accessible tool that contributes to the technical and institutional strengthening of refrigeration mechanics, promoting the appreciation and sustainability of their activities in the market.